ASPEK REPRODUKSI IKAN KAPASAN (Gerres kapas Blkr, 1851, Fam. Gerreidae) DI PERAIRAN PANTAI MAYANGAN, JAWA BARAT [Reproductive aspect of silver biddy (Gerres kapas Blkr, 1851, Fam. Gerreidae) in Mayangan Coast, West Java] - Djadja Subardja Sjafei; Dian Syaputra (Jurnal Iktiologi Indonesia, 2009)
This study was held as a fundamental management for silver biddy fish in Mayangan Coast, Subang, West Java, from June to November 2003. The main objective of the study was to determine the sex ratio, gonad maturity development, gonado somatic index, fecundity, and spawning pattern. The result showed that the sex ratio of male and female fish based on total fish and mature fish were unbalanced (1:3.06 and 1:9.26). Based on gonad maturity development it suggested that fish spawned in every month. The first size of maturity for male and female were 115 mm and 105 mm. GSI increased based on total length and gonad maturity development. The fecundity of silver biddy fish was ranged from 1.158 to 219.372 in eggs. Based on the oocyte diameter distribution from the mature fishes, the fish was indicated as total spawner.